Scorpions from the primeval subgenus Archaeotityus produce putative homologs of Tityus serrulatus toxins active on voltage-gated sodium channels - A Borges; MJ Jowers; S Bónoli; L De Sousa (Journal of Venomous Animals and Toxins including Tropical Diseases, 2012)
It has been proposed that the subgenus Archaeotityus comprises the most ancient species group within the medically important scorpion genus Tityus. cDNA encoding sodium-channel active toxins from the type species of this subgenus, Tityus clathratus (central Venezuela), have been isolated and sequenced. Two cDNAs were retrieved that encoded 61 amino acid-long putative neurotoxins named Tcl1 and Tcl2. Sequence identity was highest (87%) when both were compared with β-toxin Ts1 from the Brazilian scorpion Tityus serrulatus and its homologs from T. bahiensis, T. stigmurus, and T. costatus. A Bayesian analysis indicated statistical support for the grouping of T. clathratus Tcl1 and Tcl2 with Brazilian gamma-like β-toxins, reinforcing previous phylogenetic studies which suggested an evolutionary relationship between the subgenus Archaeotityus and scorpion species inhabiting southeast South America belonging to the subgenus Tityus.